Structural Parameters of the Thin Disk Population from Evolved Stars in the Solar Neighborhood - Sedanur İyisan; Selçuk Bilir; Özgecan Önal Taş; Olcay Plevne (The Astronomical Journal)
This study investigates the structural parameters of the thin-disk population by analyzing the spatial distribution of evolved stars in the solar neighborhood. From the Gaia Data Release 3 database, about 39.1 million stars within 1 kpc and with relative parallax errors σ _ϖ / ϖ ≤ 0.10 were selected. The photometric data was corrected for extinction using a Galactic dust map. The sample was refined by considering the color–magnitude region ${M}_{{\rm{G}}}× {(G_{{\rm{BP}}}-G_{{\rm{RP}}})}_{0}$ associated with evolved stars, applying a stricter parallax error limit of σ _ϖ / ϖ ≤ 0.02, and yielding 671,600 stars. The star sample was divided into 36 regions based on their Galactic coordinates, with evolved stars in the absolute magnitude range of −1 < M _G (mag) ≤ 4 further split into five one-unit magnitude intervals. This led to 180 subgroups whose space-density profiles were modeled using a single-component Galaxy model. The analysis shows that the space densities are in agreement with the literature and that the scale heights vary with 200 < H (pc) < 600 interval to their absolute magnitudes. Red clump stars in the solar neighborhood were also estimated to have a scale height of 295 ± 10 pc. These findings indicate that evolved stars with bright absolute magnitudes originate from the evolution of the early spectral-type stars with short scale height, while fainter ones come from the evolution of the intermediate spectral-type stars with large scale height, suggesting that variations in scale height reflect the contribution of Galactic evolution processes.